Examining the Challenges and Opportunities of Managing Public Services in a Complex and Interconnected World - Karamchand, Panini (Journal of Public Representative and Society Provision, 2021)
The paper aims at discussing extensive and diverse problems and opportunities as the phenomena of globalization shape the management of public services. This study uses surveys and interviews with the target public managers to identify research questions such as the following major challenges: political instability, economic limitations, technology change, and social disparities. The conclusions reached prove that there is great potential for digital improvement of administrative productivity and citizens’ satisfaction, but equally grand are the issues of cybersecurity, social inclusiveness, and allocation of resources. in the same regard political instability and regulatory restraints hinder strategic planning and advancement, while persistent social disparity demands efficient stakeholder management. Economic conditions, as much as they may restrain, are instrumental in spurring creativity; the case should therefore be made for sustainability analyses that combine financial realism with inventive solutions. This research points out that the development of sound and coherent theories and coherent theories in the teaching and practice of public service management, which inhibits technology adoption, social justice, political stability and fiscal viability. The research presents crucial information for policy makers and public manager interested in enhancing the anti-shock and adaptive mechanisms within the public service delivery systems in the contemporary complex world.